2010
DOI: 10.1007/s11060-010-0501-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of psychological distress in patients with intracranial tumours: the NCCN distress thermometer

Abstract: Identification of patients suffering from elevated psychosocial distress, the sources of the distress, and the necessary treatment of the distress can be rather difficult within the neurosurgical setting (e.g., lack of time, cognitive or aphasic disorders of the patients). The distress thermometer (DT) is a single-item rapid distress screening tool by use of which these difficulties can be minimized. The objective of this study was to determine the optimum DT cut-off score that would identify significant distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 40 publications
4
83
1
6
Order By: Relevance
“…It was chosen for its promise as a practical tool for use in health care settings, where longer, more detailed scales could not practically be used to screen large numbers of individuals. However, a single-item measure of dis tress has been shown to perform well when compared with longer standard distress scales in cancer patients (35). …”
Section: Discussionmentioning
confidence: 99%
“…It was chosen for its promise as a practical tool for use in health care settings, where longer, more detailed scales could not practically be used to screen large numbers of individuals. However, a single-item measure of dis tress has been shown to perform well when compared with longer standard distress scales in cancer patients (35). …”
Section: Discussionmentioning
confidence: 99%
“…However, as sensitivity of ASD-specific screening instruments was low in our study and even the IES-R as most suitable screening instrument for ASD identified only about three quarters of ASD patients correctly, to date there is no appropriate screening instrument for ASD in brain cancer patients. One recent study [54] demonstrated that the Distress Thermometer (DT; [55]), a single-item rapid screening measure, was well suited for the routine identification of brain cancer patients suffering from psychiatric morbidity as assessed via the SCID. The DT has been specifically validated for patients with brain cancer and exhibited excellent psychometric properties for application in this population [54].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study [54] demonstrated that the Distress Thermometer (DT; [55]), a single-item rapid screening measure, was well suited for the routine identification of brain cancer patients suffering from psychiatric morbidity as assessed via the SCID. The DT has been specifically validated for patients with brain cancer and exhibited excellent psychometric properties for application in this population [54]. Thus, future research could assess the ability of the DT to detect traumatic stress in patients with brain cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this ancillary project we aim to explore the prevalence and course of patients’ psychological distress on ED admission and within the hospital stay. To measure psychological distress we will use several validated instruments including the Distress Thermometer (DT) [68,69] and the positive and negative affect schedule (PANAS) [70]. Beside general distress our focus will particularly lie on anxiety and depression assessed with the Patient Health Questionnaire-4 (PHQ-4) [71].…”
Section: Methodsmentioning
confidence: 99%